Disability Awareness in Turkey and an Assessment about Accessibility of Web Pages Related to Justice by Disabled People - Ertürk, Korhan Levent; Şimşek, A. Aslı; Songür, Damla Gülseren; Şengül, Gökhan (Information World, 2014)
The people who have physical or mental disabilities which limit their movements, senses, activities or both of them are one of the groups in society. Those people have various problems in social life directly or indirectly in Turkey. Nowadays, they face many problems in accessibility on many fields such as education, healthcare, justice, social security, etc. Those individuals are willing to draw attention and resolve their problems. The level of development of countries is directly related with the solution of the aforementined problems. In this study we focused on the common terms about the people who have limited movements, senses, activities or both; and focused on the awereness of disabled people and we investigated the the accessibility of the web sites about the justice by disabled people. Making accessible of web pages will allow the disabled people to have the equal rights with the others and will also provide diversity about information and communication sources.
Keywords: Disability; Disabled people; Accessibility; Justice; Social Work